Relationship between motion verbs and prepositions of the Malay language based on conceptual structure representation and spatial representation - Rosly, Nurul Jamilah (2020)
Motion is a change from one location to another location. Motion typology definitely needsthe role of preposition as indicator and main component to express the direction of motion. Consequently, this study focuses on spatial motion and preposition that simultaneously such as (dari, daripada, ke, kepada, di, di seberang, di sekitar, di sekeliling and di sepanjang by focusing on conceptual structure perspective (abstract). This research uses data acquired from Pangkalan Data Dewan Bahasa dan Pustaka, Malaysia as material and sample of study to be analysed using Conceptual Structure Theory (CST) (Ray Jackendoff 1997 & 2011). The argument mapping consists of three main hierarchies: argument-adjunct rules, conceptual structure representation and spatial representation. Finding reveals the existence of directional spatial motion, additive motion, becoming motion and orientative motion in function of [EVENT] and [STATE] that can predict the existence of preposition such as dari, daripada, ke, kepada, di, di seberang, di sekitar, di sekeliling and di sepanjang in bound direction, directive direction and path direction. Spatial representation also demonstrates the involvement of dimension conceptualization such as DIM 0D, DIM 2 (0+E) DIR and DIM 2 (0+E) DIR. Overall, this study has shown the relationship of motion and preposition in conceptual structure representation with spatial representation.